The Development Of Computer Aided Design Learning Model In Civil Engineering Vocational Education Study Program In Universitas Negeri Semarang - Subagio, Triono; Qudus, Nur; Syamwil, Rodia (Journal of Vocational and Career Education, 2019)
Computer Aided Design (CAD) learning model in the Civil Engineering Vocational Education program in Universitas Negeri Semarang, especially 2-dimensional modeling, continues to be developed so that learning outcomes are accepted by the standards the business / construction services industry. Development of learning outcomes is inseparable from efforts to develop learning model that is used during the learning process. The development of learning models in this study focused on the development of learning methods, learning materials and CAD learning evaluation techniques. This study used the research and development using the Dick and Carrey design. The research sample was 34 students who took Computer Graphic course. The results showed that the three aspects: the development of methods, the development of teaching materials and materials and the development of evaluation techniques were categorized as excellent and very excellent. The CAD learning method was very suitable to be developed through conceptual learning methods, direct practice learning and case study learning. The use of this method was based on the needs faced in the classroom (situational). This means that the use of this method could be used at once, or varied according to the condition in the class. The use of learning equipment is one of the keys for successful learning development. The learning equipment developed in this study included the use of hand-outs, modules and supplements. The use of all three was very successful to support optimal learning outcomes. The use of all three was also aimed to facilitate the diverse learning needs of students. The development of evaluation techniques in learning included three domains: cognitive, psychomotor and affective domain. The cognitive domain was divided into two aspects: construction knowledge and the use of software. The development of evaluation techniques showed that the ability of students in each domain was in the excellent and very excellent category.